Supporting recovery: Intersections of health, belonging, and help seeking after a campus mass casualty event - Sharon Jalene; Jason A. Ciccotelli; Lauren Gatto; Christian Ison; Jaime Carbajal; Andrew Hooyman (PLoS ONE, 2026)
Mass casualty events (MCE), such as campus shootings, can severely impact the mental health of students, faculty, and staff. This study examined the psychological effects of an MCE at a minority-serving institution and explored how sense of belonging, cardiorespiratory fitness, and treatment preferences influenced recovery. To measure the impact of the MCE on mental health an anonymous survey was administered four to five months post-MCE to university students, faculty and staff. Within the survey, participants were asked to retrospectively report their depression (PHQ-9) and anxiety (GAD-7) symptoms as they recalled them two weeks prior to the MCE , and as they experienced them in the two weeks preceding survey completion. The survey also included current measures of sense of belonging (SBS), perceived discrimination (PEDQ), estimated cardiorespiratory fitness (eCRF), and intervention preference to cope with the impacts of the MCE. Participants reported significant perceived increases in PHQ-9 and GAD-7 scores from the pre-MCE recall to current time-periods. Increases in depression (PHQ-9 scores) from pre-MCE to recent recall were larger among respondents with lower pre-MCE anxiety (GAD-7 scores), higher perceived discrimination (PEDQ), and those currently receiving treatment for anxiety or depression; respondents not receiving treatment showed no significant change. Among students, lower belonging scores were associated with greater increases in depression. Neither belonging nor perceived discrimination were strongly linked to individual variables, indicating their multifactorial nature. Most participants reported a preference to learning about alternative interventions such as exercise or meditation over pursuing university counseling services.